PENGARUH TAX AVOIDANCE TERHADAP NILAI PERUSAHAAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Komang Krisma Mahaetri; Ni Ketut Muliati (Hita Akuntansi dan Keuangan, 2020)
Company value is a description of the general state of a company that can be used as an consideration of investors to invest. This research aims to determine the effect of tax avoidance on the value of companies with good corporate governance as a variable variable. Data sources used in this study are secondary data. The population in this study are all listed companies in the Indonesia Stock Exchange in 2013-2017 as many as 570 companies. The samples were used by 8 companies with a total sample of 40 observations in 5 years, through the non-probability sampling method with purposive sampling technique. The data-analysis technique used in this study is Moderated Regression-Analysis. The results of this study show that tax avoidance has a negative effect on firm value, meaning that the greater the tax avoidance, it results in a decrease in the value of the company. Good Corporate Governance is not able to moderate the relationship between tax avoidance and corporate value.